2023
DOI: 10.3389/fpsyt.2023.1179562
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the correlations between seven psychiatric disorders and the risks of breast cancer, breast benign tumors and breast inflammatory diseases: Mendelian randomization analyses

Abstract: BackgroundPrevious observational studies have showed that certain psychiatric disorders may be linked to breast cancer risk, there is, however, little understanding of relationships between mental disorders and a variety of breast diseases. This study aims to investigate if mental disorders influence the risks of overall breast cancer, the two subtypes of breast cancer (ER+ and ER-), breast benign tumors and breast inflammatory diseases.MethodsDuring our research, genome-wide association study (GWAS) data for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…We used F-statistics to evaluate the statistical strength. The Fstatistics are equal to ((N-k-1)/k) × (R2/(1-R2)), where N and k represent the sample size and number of SNP, respectively (34). An F-statistic < 10 indicates that the genetic variation used is a weak tool variable that may contribute to a bias.…”
Section: P Value and F-statistics Calculationmentioning
confidence: 99%
“…We used F-statistics to evaluate the statistical strength. The Fstatistics are equal to ((N-k-1)/k) × (R2/(1-R2)), where N and k represent the sample size and number of SNP, respectively (34). An F-statistic < 10 indicates that the genetic variation used is a weak tool variable that may contribute to a bias.…”
Section: P Value and F-statistics Calculationmentioning
confidence: 99%
“…We additionally calculated the Fstatistic to examine the statistical strength of every instrumental variable by the following formula: F=[R 2 ×(N-k-1)]/[(1-R 2 )×k], and k was the number of instrumental variables [32][33][34]. F>10 indicated that the instrumental variables were robust and could be used for MR analyses [19,35,36]. Next, we extracted SNPs for neurological diseases from the breast cancer data and eliminated the ones associated with outcomes.…”
Section: Instrumental Variable Selectionmentioning
confidence: 99%
“…Therefore, for AN and AXD we relaxed the threshold of the p-value of exposure-associated IVs in the screening condition to < 5 × 10 -5 and the linkage disequilibrium [LD] r 2 to 0.01. The settings above were previously also used in many MR studies of psychiatric disorders (30,31). The causal effect of psychiatric disorders on AS is currently analyzed using the MR analysis methods described above except for phenotype "AN", which applies only to the WR method because only one SNP is available.…”
Section: Reverse Mendelian Randomization Analysismentioning
confidence: 99%